El viaje surrealista de Joanna Domanska / The surreal journey of Joanna Domanska - María Pita Ponte; María Dolores Villaverde Solar (Asparkía, 2017)
RESUMEN: La Fundación Eugenio Granell es un centro referencial del arte contemporáneo en Galicia. Se especializa en el movimiento surrealista, vanguardia que tuvo en sus filas gran número de mujeres. Con este texto se intentará hacer una breve aproximación al Surrealismo, a la Fundación Granell y al rol que juegan las mujeres en el arte analizando cuál es su papel en la Fundación al destacar las creaciones de una de las artistas que han expuesto allí: Joanna Domanska. El Surrealismo de Joanna Domanska es actual y distinto, provocando inquietar con sus piezas donde siempre aparecen hombrecillos anónimos de espaldas, frente a algún objeto gigantesco: casas sin dueño, enormes libros, instrumentos. ABSTRACT: Eugenio Granell Foundation is a reference center of contemporary art in Galicia. It specializes in the Surrealist movement, avant-garde had in its ranks large numbers of women. The aim of this text is to make a brief reference to Surrealism, the Granell Foundation and the role that women play in art analyzing what their role in the Foundation by highlighting the creations of one of the artists who have exhibited there: Joanna Domanska. Joanna Surrealism Domanska is current and different, causing trouble with pieces where always appear anonymous little men back, facing a gigantic object: unowned houses, huge books, instruments.